Facebook Ads for Health Promotion Against Covid-19: An Environmental Medicine Perspective - Rahmad Agus Dwianto; Nur Wening; Elita Dwi Hapsari (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aims to provide innovative ideas to disseminate information on environmental medicineduring the Covd-19 pandemic via Facebook. The socialization of the environmental medicine informationtothe public was hampered during the Covid-19 pandemic. This study provides innovative informationdissemination strategies and to increase public awareness and knowledge about environmental medicine.The research method uses literature reviews from various recent studies on the use of social media Facebookfor the dissemination of information. The study found that Facebook advertising as a digital platform for thedissemination of environmental medicine during a pandemic to the public is more efficient in terms of time,energy, costs, and a wider target market. This study found innovations, namely the use of Facebook ads as adigital marketing platform for the disseminating of environmental medicine programs to the public duringa pandemic. Further studies could combine Facebook Ads with other platforms such as Google Ads, SEO,and TikTok.